Penerapan Prinsip Komunikasi Islam pada Pembinaan Karakter Mahasiswa Baru Universitas Syiah Kuala - Rahmat Saleh; Mawaddatul Husna; Zakirah Azman (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Syiah Kuala University (USK) has developed more widely and intensively the character building-oriented program, one of which is the inauguration of the Character Development Course (MKPK). As an Islamic-based student development program, the teaching process of MKPK by the mentors of UP3AI USK must be guided by the Islamic communication principles as described in the Quran and Hadith. However, the mentors did not fully implement the Islamic communication principles. This study aims to describe the Islamic communication method and analyze the applications of Islamic communication principles in the Character Development program. The theory used in this study is Aristotle’s rhetoric theory. This type of study is descriptive qualitative using interviews and documentation as the data collection method. The informants in this study are five mentors of UP3AI and one mentor coach. The results of this study indicate that the application of Islamic communication principles by mentors in the Character Development program has been going well, but still not optimal.